Penerapan Metode Wafa (Otak Kanan) Dalam Meningkatkan Hafalan Al-Qur’an Mata Pelajaran Tahfiz Qur’an Siswa Kelas VII MTs Ubudiyah Pangkalan Brandan - Meliana, Zaifatur Ridha, Ahmad Fuadi (Pusdikra Publishing, 2023)
The purpose of this study is to find out how to apply the Wafa method (right brain). To find out how to improve memorization of the Koran in students of MTs Ubudiyah Pangkalan Brandan, Langkat Regency. To find out the application of the Wafa method (right brain) in increasing Al-Qur'an memorization in MTs Ubudiyah Pangkalan Brandan Langkat students. The model in this study uses the Kurt Lewin research model which consists of 4 stages namely; planning, implementation of action, observation and reflection. The subjects of this study were in class VII MTs Ubudiyah Pangkalan Brandan using the Wafa learning method. Consisting of 35 students,. Data collection techniques using interviews, observation, documentation, and written test assessment The results of the research on student memorization increased after the wafa learning method was applied. It can be seen from the results of observations of student learning activities in cycle II that have increased compared to cycle I. The average observation cycle I was 67%, the average cycle II was 71.34 %. In cycle II there was an increase in the percentage of student learning activities of 4.34% of the cycle. While the results of learning to describe the material also experienced an increase, in the first cycle the first meeting of student learning outcomes to describe the material obtained an average value of 62.71 and the second meeting of student learning outcomes to analyze, the material obtained an average of 67. In cycle II the average learning outcomes increased, the first meeting of student learning outcomes to analyze material obtained an average score of 71.34 and the second meeting of student learning outcomes to analyze material obtained an average of 75.00. From the pretest before the action obtained an average value of 74.48 and the results of the posttest after the action obtained an average value of 87.17. If measured by N-gain, the average student ability is 0.49 in the medium category. This shows that the wafa learning method according to the students of Private MTs Ubudiyah Pangkalan Brandan is considered good, namely between the classification of 56-75%. Thus the application of the wafa learning method can improve students' material description abilities.